(untitled) (Journal of Bangladesh Academy of Sciences, 2010)
A problem on the plane inviscid and irrotational fluid motion due to the presence of a line source and sink in the region between two fixed co-axial circular cylinders is considered in terms of the stream function. It has been shown that the solution of the problem is not possible in the light of the Eulerian theory of inviscid fluid motion. Key words: Non-existence; Inviscid fluid motion; Fixed cylinder DOI: 10.3329/jbas.v34i1.5494 Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 83-87, 2010